'We are actually raising South Africans''. Raising immigrant families: The parenting experiences of Zimbabweans in South Africa - Finos, Shuvai T. (Department of Sociology, 2020)
South Africa is the most popular international destination for Zimbabwean migrants escaping the economic crisis of their country. It has been estimated that by 2016, one and a half million Zimbabwean nationals were living in South Africa. However, little research explores the lived experience of Zimbabweans in South Africa in the context of family. This is despite scholars highlighting an increase in family migration from Zimbabwe to South Africa in recent years. This study explores the parenting experiences of immigrant Zimbabwean parents raising their children in South Africa. Specifically, it investigates the ways in which raising children in a different country and cultural context influences parents’ understanding of and approaches to parenting. Nine Zimbabwean mothers and fathers living with their spouses and children in Cape Town participated in a qualitative study, with semi-structured interviews. Data was collected and analysed using thematic analysis. The study found that the participants’ overarching experience of parenting was that they were ultimately raising ‘South Africans’. Participants framed their children’s ‘South African-ness’ positively, identifying the children as cosmopolitan and empowered, which they celebrated. However, they also lamented the children’s loss of identity as the most problematic aspect of ‘South African-ness’. To navigate the resultant tensions, participants relaxed some of their existing beliefs while simultaneously implementing measures to reinforce some non-negotiable values and beliefs in their children. This dissertation argues that while parents’ understanding of parenting is strongly rooted in their cultural background and values, they adapt their parenting styles and practices according to what they calculate will enable their families to thrive. The study adds to the body of knowledge on immigrant Zimbabwean families who have become part of South African society. This is especially relevant in light of the South African government’s laudable initiatives towards regularising the stay of Zimbabweans in South Africa, such as the Dispensation of Zimbabweans Project (DZP) of 2009 and its successive permits. This study can therefore contribute to the body of knowledge that informs the ways in which South Africa can continue to respond to the reality of migration from Zimbabwe.